Upaya Peningkatan Keterampilan Membaca Pemahaman dengan Media Komik pada Siswa Kelas IV MIN 9 Aceh Tengah - Nurjani, Nurjani (YASIN, 2025)
This research started from the problem of class IV MIN 09 Central Aceh students not being able to understand the content of the literature they read. This research has an important urgency for students, namely as a provision for them to quickly understand information later. So it is hoped that the presence of comic media will make them focus on reading and be able to understand the content of the reading they read. This research uses the Classroom Action Research method, consisting of 4 stages, namely, planning, implementation, observation and reflection. The instruments in this research are first: observation, consisting of observations made to see the effectiveness of learning reading comprehension using comic media, and second: test, asking questions related to students' reading material. Based on the research conducted, there was a student's understanding of the content of reading materials using comic media from cycle I to cycle II, it can be seen as follows: in cycle 1, there were 13 students who completed it with a percentage of 53% and 12 students who did not complete it with a percentage of 48%. %. Then in cycle II only 3 students did not complete with a percentage of 12% and the remaining 22 students completed, namely getting a score of 70 and above with a percentage of 88%. So, it can be stated that the research carried out can run well.